Extraction of high added value biological compounds from sardine, sardine-type fish and mackerel canning residues - a review - Ferraro, Vincenza (2014)
Different valuable compounds, which can be employed in medicine or in other industries (i.e. food, agro-chemical, pharmaceutical) can be recovered from by-products and waste from the fish canning industries. They include lipids, proteins, bio-polymers, minerals, amino acids and enzymes; they can be extracted from wastewaters and/or from solid residues (head, viscera, skin, tails and flesh) generated along the canning process, through the filleting, cooking, salting or smoking stages. In this review, the opportunities for the extraction and the valorisation of bioactive compounds from sardine, sardine-type fish and mackerel canning residues are examined and discussed. These are amongst the most consumed fishes in the Mediterranean area; moreover, canning is one of the most important and common methods of preservation. The large quantities of by-products generated have great potentials for the extraction of biologically desirable high added value compounds.